Foreword to the special focus on advances in symbolic and numeric computation - Loja, Amélia (2017)
This special focus of Mathematics in Computer Science is connected to SYMCOMP 2015, the 2nd International Conference on Numerical and Symbolic Computation, which was held on March 26–27, 2015, in University of Algarve, Portugal. This ECCOMAS Thematic Conference was organised jointly by Mechanical Engineering Institute and University of Algarve, under the auspice of Portuguese Society of Theoretical, Applied and Computational Mechanics. The special focus contains five contributions related to different scientific areas, combining symbolic computation applications with validated numerical methods.